2019
DOI: 10.1016/j.nicl.2019.101748
|View full text |Cite
|
Sign up to set email alerts
|

Predictive markers for Parkinson's disease using deep neural nets on neuromelanin sensitive MRI

Abstract: Neuromelanin sensitive magnetic resonance imaging (NMS-MRI) has been crucial in identifying abnormalities in the substantia nigra pars compacta (SNc) in Parkinson's disease (PD) as PD is characterized by loss of dopaminergic neurons in the SNc. Current techniques employ estimation of contrast ratios of the SNc, visualized on NMS-MRI, to discern PD patients from the healthy controls. However, the extraction of these features is time-consuming and laborious and moreover provides lower prediction accuracies. Furt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 35 publications
(53 reference statements)
5
85
0
3
Order By: Relevance
“…The approaches included combinations of transfer learning, clustering [26], and nearest neighbors for enhancing the classification performance of the model. Shinde et al [27] in his work regarding the detection of Parkinson's Disease leveraged neuromelanin sensitive MRI (NMS-MRI), which can identify abnormalities in the substantia nigra (SNc) in Parkinson's Disease patients. Moreover, the author also plotted concerns over the handcrafted features based on the contrast ratio, area, and volumes of the subcortical structures [28][29][30][31].…”
Section: Related Workmentioning
confidence: 99%
“…The approaches included combinations of transfer learning, clustering [26], and nearest neighbors for enhancing the classification performance of the model. Shinde et al [27] in his work regarding the detection of Parkinson's Disease leveraged neuromelanin sensitive MRI (NMS-MRI), which can identify abnormalities in the substantia nigra (SNc) in Parkinson's Disease patients. Moreover, the author also plotted concerns over the handcrafted features based on the contrast ratio, area, and volumes of the subcortical structures [28][29][30][31].…”
Section: Related Workmentioning
confidence: 99%
“…Multiple studies have demonstrated the clinical utility and accuracy of this sequence in patients with PD (Castellanos et al, 2015;Ohtsuka et al, 2013;Ohtsuka et al, 2014;Schwarz et al, 2011). To quantify these differences, the processing techniques that are currently used are based on visual inspection, or manual region of interest drawing followed by computation of volumes, contrast ratios or radiomics features and are arduous and time-consuming (Isaias et al, 2016;Kashihara, Shinya, & Higaki, 2011;Matsuura et al, 2013;Matsuura et al, 2016;Ogisu et al, 2013;Ohtsuka et al, 2014;Reimao et al, 2015;Sasaki et al, 2006;Schwarz et al, 2011;Shinde et al, 2019). To overcome this, NMS-MRI sequence can be employed to accurately localize and create a template of the SNc that can be utilized for analysis in parkinsonian disorders.…”
Section: Introductionmentioning
confidence: 99%
“…By using 3D-CNN [57] achieved 100% accuracy on the validation and test sets for PD diagnosis. At the same time, the study in [76] discriminated PD from typical parkinsonian syndromes having 85.7% test accuracy.…”
Section: Performance Analysismentioning
confidence: 78%
“…Shinde et al proposed to differentiate PD from HC by employing a fully automated CNN with discriminative localization architecture for creating prognostic and diagnostic biomarkers of PD from Neuro-melanin sensitive MRI or NMS-MRI [76]. For this work, data have been collected from the Department of Neurology, National Institute of Mental Health and Neuro sciences (NIMHANS) which consist of MR imaging, demographic and clinical details such as gender, age at presentation, age at onset of motor symptoms, disease duration, etc., data of PD patients, atypical parkinsonian syndromes (APS) patients, multiple system atrophy (MSA) patients and progressive supranuclear palsy along with some HC as well [76]. The authors were able to capture the subtle changes in PD in the substantia nigra pars compacta (SNc) using selected features from the NMS-MRI.…”
Section: Parkinson's Diseasementioning
confidence: 99%